2015
DOI: 10.1159/000371762
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil-to-Lymphocyte Ratio Has a Better Predictive Capacity in Diagnosing Tubo-Ovarian Abscess

Abstract: Background: The aim of this study is to identify the inflammatory markers which predict a tubo-ovarian abscess (TOA) in the most accurate way. Methods: This study involves 312 women. Preoperative inflammatory markers in the study group were compared with those in the healthy control group to identify the most efficient predictor of TOA with a high sensitivity and specificity. The recommended cutoff values of the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), white blood cell count, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 20 publications
2
28
0
3
Order By: Relevance
“…reported that WBC and neutrophil counts of the TOA patients are significantly higher than healthy controls. Also, they found that NLR and PLR values are higher in TOA patients who have normal WBC values than healthy controls . In our study, we also found that age, WBC and neutrophil counts, and TOA size were significantly different between the conservative treatment group and surgical intervention group.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…reported that WBC and neutrophil counts of the TOA patients are significantly higher than healthy controls. Also, they found that NLR and PLR values are higher in TOA patients who have normal WBC values than healthy controls . In our study, we also found that age, WBC and neutrophil counts, and TOA size were significantly different between the conservative treatment group and surgical intervention group.…”
Section: Discussionsupporting
confidence: 75%
“…In a previous study which had compared TOA patients and healthy controls, NLR was statistically significant with a cut‐off value of ≥4.15 (95% CI 0.97–1.00, sensitivity 95.2%, specificity 99.4%) in the definition of TOA. In the same study, median NLR was significantly lower in healthy patients compared to TOA patients at 1.9 and 9.3 rates, respectively . Some studies attempted to establish a threshold value of NLR to predict the severity and prognosis of the disease in septic patients.…”
Section: Discussionmentioning
confidence: 95%
“…Different hematological parameters have been used to evaluate the inflammatory status of distinct disease states www. journals.viamedica.pl/ginekologia_polska in recent years [8,9]. Mean platelet volume (MPV), platelet distribution width (PDW), neutrophil-to-lymphocyte ratio (NLR), red cell distribution width (RDW) and platelet-to-lymphocyte ratio (PLR) are simple markers that have been shown to reflect inflammatory burden and disease activity in several disorders, including ulcerative colitis, spontaneous bacterial peritonitis, malignancies, and cardiovascular diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and red blood cell distribution width are novel serum inflammatory markers with higher sensitivity than other serum inflammatory markers such as CRP and WBC (13,(26)(27)(28). These markers also increase in different obstetric conditions such as spontaneous preterm delivery or gestational diabetes mellitus (17,24,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that pregnant women with HG have higher inflammatory markers when compared to healthy pregnant women without HG in the first trimester. Measuring white blood cell count (WBC), neutrophil-to-lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and red blood cell distribution width (RDW) is an inexpensive and convenient way to identify systemic inflammation in the body (12)(13)(14)(15). Studies have shown that NLR, PLR, and RDW values are highly associated with the prognosis of diseases related to inflammation (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%